EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIS SISWA - Nurjannah Harahap; Eva Yanti Siregar; Sinar Depi Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
Abstract This study aims to know whether there is a significant influence of using problem based learning (PBL) model reviewed from students’ mathematical reasoning ability on the topic of two-variable linear equation system at the tenth grade students of SMK Negeri 1Batang Angkola. The research was conducted by applying experimental method (one group pretest post test design) with 30 students as the sample and they were taken by using simple random sampling technique from 130 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using PBL model was 2.90 (good category) and (b) the average of students’ two-variable linear equation system achievement before using PBL model was 53,02 (fair category) and after using PBL model was 87.51 (very good category). Furthermore, based on inferential statistic by using pair sample ttest (SPSS 22), the result showed significant value was less than 0.05(0.000<0.05). It means there is a significant influence of using PBL model reviewed from students’ mathematical reasoning ability on the topic of two-variable linear equation system at the tenth grade students of SMK Negeri 1Batang Angkola. Keywords: PBL, students’ mathematical reasoning ability